2018
DOI: 10.4103/ijciis.ijciis_33_18
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and clinical skill of emergency medical technicians from Tehran emergency center in trauma exposure

Abstract: Introduction:Prehospital care is the first part of the trauma treatment and care system. Diagnostic and therapeutic measures taken before these patients arrive at the hospital plays significantly reduce mortality and improve their outcomes. Therefore, the present study aimed to determine the knowledge, attitude, and clinical skill of emergency medical technicians in Tehran Emergency Center in trauma exposure.Methods:In this descriptive study, 213 participants were selected through stratified random sampling. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Health care workers who got training were 2 times (AOR = 2.25(95%CI: 1.33, 4.52)) more likely to have good knowledge as compared to their counterparts towards pre-hospital care. This is similar with study done in Indonesia showed that, training had a signi cantt in uence on the knowledge, attitude, and practice scores for pre-hospital care [19].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Health care workers who got training were 2 times (AOR = 2.25(95%CI: 1.33, 4.52)) more likely to have good knowledge as compared to their counterparts towards pre-hospital care. This is similar with study done in Indonesia showed that, training had a signi cantt in uence on the knowledge, attitude, and practice scores for pre-hospital care [19].…”
Section: Discussionsupporting
confidence: 89%
“…A study done in Tehran showed that the level of knowledge regarding trauma and its management was good in 17.4% (37), average in 81.1% (173), and weak in 1.4% [19]. In similar manner a study in India showed that, 87.50% of nursing students and 72.50% of nursing staff knew the de nition and abbreviation of BLS.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…According to the World Health Organization (WHO), injuries caused by trauma are the main reasons for death in different countries and up to 2020, trauma will be the third cause of death and disability in different age groups (1). Emergencies are high-risk situations in which individuals' physical or mental conditions are suddenly affected, requiring immediate and appropriate actions to be taken (2,3). To reduce the morbidity and mortality rate of trauma, an appropriate planning for the care and treatment of these patients is needed.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, an initial diagnosis of the lesions, triage of the injured and early resuscitation occurs. The successful operation of the pre-hospital system will play a crucial role in patients' outcome (1,3). The most critical and important part of the emergency medical services (EMS) is the competent paramedics (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%